Pengaruh Literasi Digital, Pengetahuan Kewirausahaan dan Lingkungan Keluarga terhadap Minat Berwirausaha Mahasiswa dengan Efikasi Diri sebagai Variabel Intervening (Studi Kasus Mahasiswa Universitas PGRI Semarang Angkatan 2021-2022) - Novita sari; Ika Indriasari; Prianka Ratri Nastiti (Fakultas Ekonomi dan Bisnis Universitas PGRI Semarang, 2025)
This study aims to analyze the effect of digital literacy, entrepreneurial knowledge, and family environment on entrepreneurial interest with self-efficacy as an intervening variable. The population in this study were 7,715 students of PGRI Semarang University class of 2021-2022 with a sample size of 380 people. The data collection techniques used were distributing questionnaires via Google Form and by distributing them directly in the PGRI Semarang University campus environment. The analysis method uses Structural Equation Modeling (SEM). By using probability sampling technique. The results showed that: (1) digital literacy has a positive and significant effect on self-efficacy; (2) entrepreneurial knowledge has a positive and significant effect on self-efficacy; (3) family environment has no effect on self-efficacy; (4) digital literacy has a positive and significant effect on entrepreneurial interest; (5) entrepreneurial knowledge has a positive and significant effect on entrepreneurial interest; (6) family environment has a positive and significant effect on entrepreneurial interest; (7) self-efficacy has a positive and significant effect on entrepreneurial interest; (8) digital literacy has a positive and significant effect on entrepreneurial interest mediated by self-efficacy; (9) entrepreneurial knowledge has a positive and significant effect on entrepreneurial interest mediated by self-efficacy; (10) family environment has no effect on entrepreneurial interest mediated by self-efficacy. Keywords: Digital Literacy 1; Entrepreneurial Knowledge 2; Family Environment 3; Self-Efficacy 4; Entrepreneurial Interest 5.